The making of an economist, redux - Colander, David C. (Princeton University Press, 2007)
"Shows what is happening in elite U.S. economics Ph. D. programs, providing a view of cutting-edge economics and a glimpse at its likely future ... Also shows how much--and in what ways--the field has changed over the past two decades"--Publisher description